Proceedings of Surabaya International Physiology Seminar 2017
DOI: 10.5220/0007333601010105
|View full text |Cite
|
Sign up to set email alerts
|

Sauropus Androgynus for Increasing Uterine Weight in Menopausal Women: An Experimental Study Using Animal Models

Abstract: Menopause is a natural phase of life and happens in every woman who reaches a certain age. This condition has many problems, such as endometrial atrophy, which can cause abnormal bleeding. Sauropus androgynus, known as Katu Leaf, has isoflavones compound and acts as an estrogen-like agent or phytoestrogen. Isoflavone can induce cell proliferation activity in increasing endometrial thickness and uterine weight. This study was aimed to find how the is flavone compound in Sauropus androgynus can increase the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Katuk leaves (Sauropus androgynus) contain secondary metabolite compounds such as sterol compounds, tannins, saponins, terpenoids, phenols, and (Awaludin et al 2020) Potential estrogenic effects on S. androgenus have an impact on the reproductive process, and katuk extract has direct and indirect effects on the reproductive system, which is related to estrogen receptors; apart from that, it also contains iso avone compounds and acts as an agent similar to estrogen and phytoestrogen which shows potential estrogenic properties (Hikmah & Susilowati, 2017;Susilowati et al, 2020). Each treatment group with the addition of katuk extract showed high HSI values, which proves that the estrogen compounds contained in katuk extract stimulate growth and development of the livers of cat sh.…”
Section: Discussionmentioning
confidence: 99%
“…Katuk leaves (Sauropus androgynus) contain secondary metabolite compounds such as sterol compounds, tannins, saponins, terpenoids, phenols, and (Awaludin et al 2020) Potential estrogenic effects on S. androgenus have an impact on the reproductive process, and katuk extract has direct and indirect effects on the reproductive system, which is related to estrogen receptors; apart from that, it also contains iso avone compounds and acts as an agent similar to estrogen and phytoestrogen which shows potential estrogenic properties (Hikmah & Susilowati, 2017;Susilowati et al, 2020). Each treatment group with the addition of katuk extract showed high HSI values, which proves that the estrogen compounds contained in katuk extract stimulate growth and development of the livers of cat sh.…”
Section: Discussionmentioning
confidence: 99%
“…Some phytoestrogens are diosgenin, anethole estragole, shatavarine silybin, kaempferol, quercetin, silydianin, silychristin 7 . Damanik et al (2017) found that in Torbangun leaves, there are digiprolactone and kaempferol derivatives (flavonoids of the flavonol group) 22,23 , while Katuk leaves contain isoflavones and quercetin as phytoestrogens 24 . The galactagogue mechanism of phytoestrogens occurs in anterior pituitary lactotrophic cells and the mammary glands.…”
Section: Introductionmentioning
confidence: 99%